1989
DOI: 10.1007/978-94-009-2565-6_30
|View full text |Cite
|
Sign up to set email alerts
|

Babassu palm in the agroforestry systems in Brazil’s Mid-North region

Abstract: Babassu palms (Orbignya spp.) cover nearly 200,000 km 2 in Brazil, providing cash income, fuel, fibre, edible oil and food to a large number of tenant farm households. Babassu is closely integrated within pastoral and shifting cultivation systems of Mid-North Brazil. In pastures, babassu provides shade for cattle, aids soil moisture retention, produces organic matter, generates supplementary farm income at little cost, and offers year-round employment. On the other hand, the persistence of juvenile palms reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
0
11
0
3
Order By: Relevance
“…ex Spreng.) in northeast Brazil, which is integrated into local farmers' shifting cultivation systems [168], and fruit trees planted at an early stage in agricultural settlements [169]. Research and development practitioners must start thinking about ways to develop innovative roles for agro-ecosystems and heterogeneous landscapes, so as to ensure that food production systems and value chains are more nutrition-sensitive, while minimizing their ecological footprint [1].…”
Section: Integrating Forest Biodiversity Into Complex Landscapes Manamentioning
confidence: 99%
“…ex Spreng.) in northeast Brazil, which is integrated into local farmers' shifting cultivation systems [168], and fruit trees planted at an early stage in agricultural settlements [169]. Research and development practitioners must start thinking about ways to develop innovative roles for agro-ecosystems and heterogeneous landscapes, so as to ensure that food production systems and value chains are more nutrition-sensitive, while minimizing their ecological footprint [1].…”
Section: Integrating Forest Biodiversity Into Complex Landscapes Manamentioning
confidence: 99%
“…If the arboreal accumulation of organic matter and the funneling of water by babassu palms is the primary mechanism that enriches stemflow, we would expect this effect to be greater during the wet season when rainfall solute concentrations are low compared with the dry season or early wet season when rainfall solute fluxes and fluxes originating from dry deposition are higher (Germer et al, 2007). Slash-and-burn systems that include babassu palms are widespread in northeastern Brazil (Gehring et al, 2011;May et al, 1985). Recent research focuses on agroforestry with permanent vegetation cover including babassu palms as an alternative for slash-and-burn (Moura et al, 2009).…”
Section: Stemflow Solute Concentrations Of Trees and Palmsmentioning
confidence: 99%
“…In many situations, fallow land, farm bush and even the forest itself have in fact been found to be actively managed by local users to conserve or encourage species of value. The babaçu palm (Orbygnia phalerata) in northeast Brazil has long been integrated into local farmers shifting cultivation systems (May et al 1985), and farmers in the flood-plain forests of the Amazon area manage them to favour the economically more valuable species they contain . Rattan and fruit gardens are examples of enriched forest management systems in Kalimantan (Peluso and Padoch 1996).…”
Section: Role Of Ntfps In Conservation and Developmentmentioning
confidence: 99%
“…Income from the collection and processing of babaçu palm kernels in northeast Brazil has been shown to account for 39 per cent of cash income and 34 per cent of total household income during the seasonal slack period in agriculture. Many of the poorer farmers were dependent on this cash for purchasing seed and other inputs for the new season s planting (May et al 1985). A study in the forest-savanna zone of Guinea found that needs for fuelwood and poles were mainly met from by-products of the agricultural cycle, and that farmers sequence their wild plant collection and trading incomes with seasonal needs, e.g., to purchase seeds, hire labour for cultivation, and buy food at harvest to be processed and sold during the dry season.…”
Section: Box 21 Examples Of the Role Of Ntfp Income In Household Sysmentioning
confidence: 99%